Technical and Sociocultural Aspects in Sustainable Urban Forest Management in Dolok Sanggul District - Damanik, Sarintan Efratani; Oktavianus, Maju Harry (Institut Pertanian Bogor (IPB University), 2024)
Urban forest management is crucial for urban development, significantly contributing to environmental, economic, and social well-being. Dolok Sanggul District, in Humbang Hasundutan Regency, offers a unique context for examining technical and sociocultural aspects of urban forest management. This research aims to analyze these aspects' influence on urban forest management in Dolok Sanggul District using a quantitative research method and multiple regression analysis. The study's results indicate that both technical and sociocultural aspects significantly impact urban forest management. Technical aspects, such as law and regulation regarding forestry, account for 51.0% of the influence. Sociocultural aspects, including community opinions on community awareness and participation, education and the social environment, as well as community interaction, contribute 55.2%. Combined, these aspects exert a synergistic effect, with a total influence of 63.4% on urban forest management. These findings underscore the importance of integrating technical and sociocultural considerations to develop effective urban forest management strategies. By leveraging the strengths of both aspects, policymakers and urban planners can create sustainable and resilient urban forests that benefit the community and environment. Additionally, this research highlights the need for a holistic approach that values community input and technical expertise, ensuring balanced and sustainable urban development. This study provides a foundation for future research and practical applications, emphasizing the critical role of comprehensive planning and community engagement in urban forest management.